The Post-API Age of Social Media Data Access: Past, Present, and Future. - Freelon, Deen; Monzer, Cristina; Jeon, Gayoung; Moy, Cameron; Williams, Natasha (Annals of the American Academy of Political & Social Science, 2024)
Social media data have become a mainstay of social science research since the first application programming interfaces (APIs) debuted in the mid-2000s. Over time, platforms have radically altered their data offerings, substantially determining the kinds of research that can be conducted. This article presents historical and normative analyses of the current state of platform data precarity, defined by Freelon (2018) as the post-API age. We recount a periodized history of social media data access spanning nearly 20 years, characterize the data access options currently offered by six prominent platforms, and make recommendations for improving platform data access. Our primary aim is to help social media researchers understand how access to social media data has evolved over the years and consider how platforms might help them conduct more rigorous research moving forward.